What Are the Maternal and Neonatal Outcomes of Adolescent Pregnancy in Women Referring to Ayatollah Mousavi Hospital in Zanjan? A Comparative Cross-sectional Study - samane yoseflu; Mahnaz Keshavarz Afshar; Mina Mousavi; Zahra Moradi; mojdeh banaei; Fatemeh Bayat (Zanjan University of Medical Sciences and Health Services, 2019)
Background: Adolescent pregnancy is considered a high-risk pregnancy and is considered as a common phenomenon in Iran. Objectives: This study aimed to compare neonatal and maternal outcomes in adolescent mothers with those of adult pregnancy. Methods: This cross-sectional comparative study was conducted between September 2018 and March 2019 in the Referral Hospital of Ayatollah Mosavi of Zanjan, Iran. Data were collected using the convenience sampling method. Overall, 133 and 696 out of 1340 participated women were teenage and adult women within the age range of 20-30 years, respectively. The Chi-squared and logistic regression tests were used to compare the neonatal and obstetric consequences of the pregnancy of the two age groups. Finally, SPSS25 was used for data analysis, and a P<0.05 was considered statistically significant. Results: Prevalence of adolescent pregnancy was found to be 9.92%. Adolescents had an increased risk of induced vaginal delivery (IVD) (OR=1.43, (OR: Odds ratio) 95% CI 1.07-4.23(CI: Confidence interval)), (P=0.01), dystocia (OR=3.23, 95% CI (2.27-17.22), (P=0.004)), and episiotomy ((OR=3.63), 95% CI (2.44-7.31), (P=0.001)). None of the neonatal consequences showed any significant difference between the two groups (P>0.05). Conclusion: In our society, adolescent pregnancy is accompanied by dire consequences for the mother, but not for the neonate. Thus, it is recommended that health workers discourage adolescent pregnancy through appropriate services and education, and in cases where pregnancy has already occurred, support the woman through offering health services in order to prevent or minimize the risks or complications of pregnancy at such early age.